Solid biofuel combustion or electrification for limestone calcination: Effects on quicklime surface microstructure. (15th October 2022) - Sandström, Karin; Eriksson, Matias; Broström, Markus
Highlights: A detailed description of ash-limestone interactions involving ash from biomass coal. A mechanistic description of ash infiltration is provided. Comparative quicklime microstructure from electrically heated calcination. Quicklime coarsening and reduced Ca-levels for both tested ashes. A salt melt was suggested to cause the quicklime coarsening with olive pomace ash. Abstract: Net CO2 emissions from the production of quicklime can be reduced by introducing renewable solid fuels or sustainably produced electricity for heating of the process. This paper reports the results of a study examining the effects of new heat sources on quicklime surface reaction products and on quicklime microstructure. Limestone was heated to 1100 °C and 1350 °C in high CO2 atmosphere under three conditions: i) an ash mixture representing conventional coal and a solid biofuel (olive pomace); ii) olive pomace ash, and iii) no ash representing an electrically heated process. The ash-quicklime interfaces of the samples were analyzed for elemental composition and microstructure using SEM-EDX. Multi-component chemical equilibrium calculations were used to assess the stable chemical phases in the interface. Coal-olive pomace ash mixture resulted in coarsening of the quicklime microstructure; this effect was less severe compared to that of pure olive pomace ash. The calculations indicated that the potassium in olive pomace ash was bound to Si- and Al-rich coal ash phases. Exposure to potassium-rich olive pomace ash resulted in severe coarsening of the quicklime microstructure. The difference was most obvious at 1, 350 °C, and was probably the result of intrusion of a potassium-rich salt melt. For limestone without ash, the quicklime showed enhanced sintering and reduced porosity at the higher temperature, in agreement with previous studies. Interface reactions and microstructure coarsening, here most apparent for the case with olive pomace, could be problematic in industrial quicklime production since they may contribute to decreased available CaO and reactivity.